Metode Penulisan Sejarah Kitab Tarikh Al-Umam Wa Al-Muluk Karya Al-Thabari: Indonesia - Alamshah, Anisah; Pababbari, Musafir; Syukur, Syamzan (Rihlah: Jurnal Sejarah dan Kebudayaan, 2023)
Tarikh al-Umam wa al-Muluk, also known as Tarikh al-Rusul wa al-Muluk, is a significant work in Islamic historiography.While it is widely acknowledged as a primary source in classical Islamic studies, it has been criticized for its perceived lack of systematic and interpretative style. Consequently, there has been a preference for Orientalist works that are deemed more rational and critical. This research study uses a descriptive-analytical approach to delve into the life and writings of Al-Thabari, a prominent scholar of the Abbasid era. The study suggests he was born in 225 AH and died in 310 AH, with his work heavily influenced by his socio-political context. Tarikh al-Umam wa al-Muluk" is recognized as one of Al-Thabari’s major achievements, covering human history before and after Islam’s rise. The book is divided into two periods: pre-Islamic and Islamic eras, discussing topics like Prophet Muhammad’s life, Mecca and Medina, wars, the Rightly Guided Caliphs, Umayyad Dynasty, and Abbasid Dynasty. Al-Thabari employed a chronological approach, relying on narrations, chains of transmission, and various sources. However, criticisms exist, including its alleged omission of important events, like the Umayyad Dynasty’s rule in Andalusia. The book is seen as lacking objectivity due to its descriptive-narrative nature and the inclusion of fictional stories. Therefore, a critical and rational historical approach is essential to evaluate the accuracy of the narratives presented in the book. Keywords: Tarikh wa al-muluk, al-thabari, traditional Islamic historiography, criticism, writing method.